THE ROLE OF FLUOROSCOPIC PROCEDURES IN THE DETECTION OF EARLY COMPLICATIONS POST SLEEVE GASTRECTOMY - Dr. Sawsan Ahmed Awadallah Osman (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: The prevalence of obesity is increasing worldwide, including in some developing countries with previously very low prevalences (WHO, 1998). The result of chronic positive energy balance, obesity is associated with many chronic diseases, such as diabetes, heart disease, hypertension and some forms of cancer (WHO, 1998). The sleeve gastrectomy operation is a very effective procedure to help overweight patients achieve a substantial and long term weight loss. It works by restricting the portion sizes and the types of food that the patient can eat. Diagnosing of post sleeve gastrectomy early complications is done using fluoroscopy to identify normal radiographic findings and possible complication after sleeve surgeries by using fluoroscopy. Methodology: This study is Prospective hospital-based Study using data from a private obesity center, with an aim of diagnosing the postoperative complications after sleeve gastrectomy using fluoroscopy on patients whose ages between (18-55) years old during the period from January to December 2023. Data was collected by check list from using Picture Archive and Communication System (PACS), based on patient’s records and data collection sheet. This study depends on the practical scanning using fluoroscopic unit for detection of upper gastrointestinal series (UGS). Results: The result of complications frequency for post sleeve gastrectomy showed that (61) patients approximately (70%) were without complications while (26) patients has had complications Out of 87 patients, who underwent UGS. Conclusion: Patients underwent sleeve gastrectomy should undergo thorough preoperative nutrition assessment and instruction conducted by a registered dietitian.